Budget Participation and Managerial Performance in Local Government: Leader–Member Exchange as Relational Governance Mediator - Sri Widodo; Wiyasto Dwi Handono; Vidya Devia Ardania; Tri Siwi Nugrahani (Yayasan Darussalam Bengkulu, 2026)
Background: Managerial performance in local government organizations remains a persistent governance challenge, as formal administrative reforms and participatory budgeting mechanisms have demonstrated limited and inconsistent capacity to produce effective organizational outcomes. Existing literature has predominantly conceptualized budget participation and information asymmetry as isolated technical variables, leaving the relational governance mechanisms connecting these constructs to managerial effectiveness substantially underexplored. Method: This study employs a quantitative explanatory design using cross-sectional survey data collected from 178 officials within Local Government Organizations (Organisasi Perangkat Daerah/OPD) in Bantul Regency, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4, with Leader–Member Exchange (LMX) positioned as a relational governance mediator. Results: Budget participation positively affects managerial performance (β = 0.210) and LMX quality (β = 0.675), while information asymmetry exerts significant negative effects on both managerial performance (β = −0.179) and LMX (β = −0.536). LMX strongly influences managerial performance (β = 0.650) and significantly mediates both relationships, confirming its role as a primary relational governance mechanism. Conclusion: Governance effectiveness in local government is fundamentally relational rather than procedural. The findings resonate with Islamic governance principles of shura, amanah, and adalah, suggesting that participatory, transparent, and trust-based governance practices are essential for sustained managerial effectiveness in public sector institutions.